2008
DOI: 10.4097/kjae.2008.54.1.58
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Female Hormones on Postoperative Nausea and Vomiting

Abstract: Background: Postoperative nausea and vomiting (PONV) is one of the most common complaints following laparoscopic surgery, and being female is a risk factor for PONV. Therefore, we conducted this study to determine if the incidence of PONV is associated with variations in the blood concentration of female hormones that occur during different stages of the menstrual cycle.Methods: We recruited 103 women who were undergoing gynecological laparoscopic surgery under general anesthesia and met all of the inclusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…In the early postoperative period, the incidence of nausea but not of vomiting was decreased during the luteal phase. The results of this study were similar to studies that suggested that the early phase of the cycle increases risk of PONV [9][10][11], but differed with those that determined that the luteal phase was a predictor of PONV [12,13] and likewise to those studies that found no influence of the cycle on PONV [14,16,17]. Small, single-center studies may not have enough power to answer the question, but a subsequent metaanalysis may be helpful.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In the early postoperative period, the incidence of nausea but not of vomiting was decreased during the luteal phase. The results of this study were similar to studies that suggested that the early phase of the cycle increases risk of PONV [9][10][11], but differed with those that determined that the luteal phase was a predictor of PONV [12,13] and likewise to those studies that found no influence of the cycle on PONV [14,16,17]. Small, single-center studies may not have enough power to answer the question, but a subsequent metaanalysis may be helpful.…”
Section: Discussionsupporting
confidence: 65%
“…This fact may explain the controversial results reported on the influence of menstrual cycle on PONV after gynecological laparoscopy (Table 1). Only three abstracts and one paper have attempted to correlate hormonal levels, with completely different results [5,16,17,20]. One report suggested that higher estradiol levels increased risks for PONV [5]; another showed that the lower levels were associated with PONV in the perimenstrual phase but not across the cycle [20]; a third report stated that PONV patients had lower mean estradiol levels regardless of cycle [16], and finally, the paper (in Korean) that suggested that estradiol had no influence on PONV at all [17].…”
Section: Discussionmentioning
confidence: 99%